2016
DOI: 10.1093/hmg/ddw288
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-Blood Transcriptome Meta-Analysis Identifies Gene Expression Signatures of Cigarette Smoking

Abstract: Cigarette smoking is a leading modifiable cause of death worldwide. We hypothesized that cigarette smoking induces extensive transcriptomic changes that lead to target-organ damage and smoking-related diseases. We performed a metaanalysis of transcriptome-wide gene expression using whole blood-derived RNA from 10,233 participants of European ancestry in six cohorts (including 1421 current and 3955 former smokers) to identify associations between smoking and altered gene expression levels. At a false discovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
129
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(143 citation statements)
references
References 66 publications
11
129
3
Order By: Relevance
“…These genes overlapped remarkably with genes present in previously published blood-based smoking gene signatures derived from the same datasets, constituting an independent confirmation of a signature proposed by Martin et al [27] and signatures from a meta-analysis of six studies that included a total of 10,233 subjects [50]. Many genes of the consensus signature are reported to undergo differential regulation at the mRNA and/or DNA methylation level following exposure to cigarette smoke (references in Supplementary table 7).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These genes overlapped remarkably with genes present in previously published blood-based smoking gene signatures derived from the same datasets, constituting an independent confirmation of a signature proposed by Martin et al [27] and signatures from a meta-analysis of six studies that included a total of 10,233 subjects [50]. Many genes of the consensus signature are reported to undergo differential regulation at the mRNA and/or DNA methylation level following exposure to cigarette smoke (references in Supplementary table 7).…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the consensus blood smoking signature may not only include genes that reflect a response to smoke exposure, but also genes that may play roles in smoke-related disease pathogenesis in the long term. This hypothesis was supported by Huan et al who found significant associations between their whole blood-based cigarette smoking signature and human complex diseases and traits [50]. …”
Section: Discussionmentioning
confidence: 69%
“…A previous transcriptome meta‐analysis reported the top 25 smoking‐related genes associated with current smokers versus never smokers . Comparing our 100 smoking genes identified in C‐SM versus C‐NSM with the top 25 smoking‐related genes identified in this previous meta‐analysis ( n = 25), we found three genes (GPR15, LRRN3, and CLDND1) overlapped, which is highly significant based on a hypergeometric probability test ( P < 0.0002).…”
Section: Discussionmentioning
confidence: 99%
“…GPR15 is an orphan receptor that is involved in the regulation of the innate immunity and T‐cell trafficking . GPR15 and LRRN3 have DNA methylation loci in their promoter regions that are reported to be hypomethylated among smokers which might indicate smoking‐induced epigenetic changes . LRRN3 is an inflammatory regulatory gene related to T‐cell function and immunosenescence whose expression declines with age and smoking, perhaps resulting in a dysregulated immune system prior to and after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…lithium users) and non-lithium users included the following variables: BD diagnosis, age, sex, tobacco use, assessment group, RIN, sequencing plate, and sequencing metric PCs 1 through 3. Tobacco use was included because of its well-characterized effect on whole blood gene expression 30 . An overview of covariates can be found in Table S1.…”
Section: Methodsmentioning
confidence: 99%